Penerapan Model Contextual Teaching and Learning dalam Meningkatkan Kemandirian Belajar Kewarganegaraan pada Siswa Kelas IV MIN Thullab Kota Jambi Tahun Ajaran 2023/2024 - Nainggolan, Ahmad Sayuti; Damayanti, Vita (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This research aimed to increase student self-regulated learning using Contextual Teaching and Learning (CTL) in fourth grade students at Madrasah Ibtidaiyah Nahdlatuth Thullab Jambi City. This study was a Classroom Action Research (CAR) consisting of cycles that included planning, implementation, observation, and reflection. The research comprised two cycles, with each cycle containing two meetings. The research subjects were 30 students in fourth grade at MIN Thullab Jambi City. In the Pre-Cycle, the average self-regulated learning based on observation results was 38%, categorized as less. In Cycle 1, the average increased to 50.5%, categorized as self-sufficient. In Cycle 2, the average further increased to 83.5%, categorized as very self-regulated. The results of this study indicate that the application of the CTL can effectively enhance the self-regulated learning of fourth grade students in Civic Education at MIN Thullab Jambi City.